Phytochemical analysis of salal berry (Gaultheria shallon Pursh.), a traditionally-consumed fruit from western North America with exceptionally high proanthocyanidin content - Geraldine Gourlay; Elisabete Carvalho; Stefan Martens; C. Peter Constabel; Juha-Pekka Salminen; Vincent Walker; Andrew Ferguson (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Salal (Gaultheria shallon Pursh.) is a wild perennial shrub of the Ericaceae and common in coastal forests of western North America, and its berries were an important traditional food for First Nations in British Columbia. Salal berries were investigated for phytochemical content and antioxidant capacity over the course of fruit development. The proanthocyanidin content was extremely high in young berries (280.7 mg/g dry wt) but dropped during development to 52.8 mg/g dry wt. By contrast, anthocyanins accumulated only at the late berry stages. Total antioxidant capacity, as measured by the 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) method, reflected both proanthocyanidin and anthocyanin content, and in mature berries reached 36 mmol Trolox equivalents/100 g dry wt. More detailed phytochemical analysis determined that delphinidin 3-O-galactoside is the dominant anthocyanin, and that the berries are also rich in procyanidins, including procyanidin A2 which has been implicated in anti-adhesion activity for uropathogenic E. coli. Proanthocyanidins were 60% prodelphinidin, and overall concentrations were higher than reported for many Vaccinium species including blueberry, lingonberry, and cranberry. Overall, the phenolic profile of salal berries indicates that these fruit contain a diversity of health-promoting phenolics. (C) 2018 Elsevier Ltd. All rights reserved.